2021
DOI: 10.1111/vde.12973
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of lactoferricin solution against Malassezia pachydermatis from otitis externa in dogs and cats

Abstract: Background -Malassezia pachydermatis is a commensal organism of the skin, yet it may induce dermatitis and/or otitis. Lactoferricin (Lfcin) is an antimicrobial peptide obtained by the pepsin-mediated digestion of lactoferrin, a multifunctional innate-defence milk protein. The antibacterial activity of Lfcin is thought to cause alteration of bacterial membrane permeability, thus inducing cell death.Objectives -The aim of this study was to evaluate in vitro antifungal activity of different dilutions of Lfcin sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For instance, Cafarchia et al (2014) found that a synthetic peptide showed antifungal activity in dogs with otitis, reducing clinical signs and yeast counts in cytological evaluation. Another study found that a peptide derived from milk protein, lactoferricin, exhibited antifungal activity against M. pachydermatis in vitro (Corona et al, 2021). In addition, the natural monoterpenoid β-thujaplicin was found to have antimicrobial activity against M. pachydermatis in both in vitro and in vivo studies (Nakano et al, 2005(Nakano et al, , 2006.…”
Section: Chemical Substancesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Cafarchia et al (2014) found that a synthetic peptide showed antifungal activity in dogs with otitis, reducing clinical signs and yeast counts in cytological evaluation. Another study found that a peptide derived from milk protein, lactoferricin, exhibited antifungal activity against M. pachydermatis in vitro (Corona et al, 2021). In addition, the natural monoterpenoid β-thujaplicin was found to have antimicrobial activity against M. pachydermatis in both in vitro and in vivo studies (Nakano et al, 2005(Nakano et al, , 2006.…”
Section: Chemical Substancesmentioning
confidence: 99%
“…Recent years have seen significant advancements in alternative treatments for otitis externa caused by M. pachydermatis in dogs (Bismarck et al, 2020;Cafarchia et al, 2014;Chan et al, 2018a;Cole et al, 2007;Corona et al, 2021;Di Cerbo et al, 2016;Ebani et al, 2020;Mason et al, 2013), to help veterinarians in their routine. The search strategy for this review revealed several articles, summarized in Table 1.…”
Section: Treatment Alternatives For M Pachydermatis Otitismentioning
confidence: 99%
See 1 more Smart Citation
“…Other novel antimicrobial compounds include various essential plant oils and extracts [60][61][62][63][64][65] , manuka honey 43 , antimicrobial peptides 66,67 , lactoferricin 68 and trisEDTA/monensin 69 . Early studies show good in vitro efficacy, although this can be more varied in the presence of mature biofilms 60 .…”
Section: Future Anti-inflammatory and Antimicrobial Treatment Optionsmentioning
confidence: 99%